Planning & perfoming yam disease phenotyping - Dr. Kolade Fisayo - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
A seminar presentation on “Planning and Performing Yam Disease Phenotyping” by Dr. Olufisayo Kolade at the International Institute of Tropical Agriculture (IITA)